PERLINDUNGAN ITUKUM TERHADAP PEREMPUAN SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA - Fenty U. Puluhulawa (Universitas Negeri Gorontalo, 2009)
Ihe housed crirne is one of the action against the Act No 39 year 1999 of Human Right, Act No 23 year 2004 of obliteration of housihold crime. As well, this hosedhold crimeis one of the offense toward the Internotional convention of Elimination of All forms of Discrimination Agains Woman (CEDAW). The emerging of the regulation of crime toward womem based on the throught that citizens hold the right to obtain the savety feeling end free from all crime beased on our basic constitution and the Purcasila Based on thoose thought, househotd crime and discrimination toward woman has to be elimination. therefore, the victim of the household crime, which mostly woman, have to obtain protectionfrim the government ang the communigt. this is in order to make them ovolded from crime or crime threats, torture, and anyother action which disgracing the human pride. Substantialy, Indonesian has many low tools to regulate this problem. In fact, the implementation and aplication of thoose regulation are not as it is expected rherefore it dis belief from the society toward the low it self. there fore, socialization to all parts of the society needs to be done in order to minimazed the household crime action